First-line immune checkpoint inhibitors in older adults (≥75 years) with advanced esophageal squamous cell carcinoma: efficacy and safety - Zheng, Lin-lin; Jiang, Yu-cai; Lin, Dan-dan (Frontiers in Oncology, 2026)
BackgroundThe combination of immune checkpoint inhibitors with chemotherapy is a standard first-line treatment for advanced esophageal squamous cell carcinoma. However, robust data regarding the efficacy and safety of this approach specifically in patients aged 75 years and older are scarce, as this population is frequently underrepresented in pivotal clinical trials.ObjectiveThis study aimed to evaluate the real-world treatment outcomes and safety profile of first-line immunotherapy in patients aged ≥75 years with advanced esophageal squamous cell carcinoma.MethodsWe conducted a retrospective, single-center cohort study. Sixty-one patients aged ≥75 years with histologically confirmed, advanced esophageal squamous cell carcinoma (stage III/IV) who initiated first-line immune checkpoint inhibitors (as monotherapy or combined with chemotherapy/antiangiogenic therapy) between February 2021 and May 2025 were included. Assessments included tumor response per RECIST 1.1, progression-free survival, overall survival, and adverse events graded per the National Cancer Institute Common Toxicity Criteria v5.0.ResultsThe median age was 80 years. The objective response rate was 45.9% (28/61), and the disease control rate was 85.2%. After a median follow-up of 16.7 months, the median progression-free survival was 12.7 months (95% CI: 6.9-17.1), and the median overall survival was 17.7 months (95% CI: 10.7-22.8). Both progression-free survival and overall survival significantly differed among response groups (log-rank p < 0.0001). Treatment was generally tolerable. Any-grade immune-related adverse events occurred in 39.1% of patients, with grade ≥3 events in 1.6%. Non-immune toxicities were common (any grade 93.1%; grade ≥3 in 14.7%), primarily hematologic.ConclusionIn this real-world cohort, first-line immunotherapy demonstrated promising efficacy and a manageable safety profile in patients aged ≥75 years with advanced esophageal squamous cell carcinoma. These findings provide valuable preliminary evidence supporting the use of immune checkpoint inhibitors in this understudied population and highlight the need for prospective validation to optimize therapeutic strategies.